Single-Cell Transcriptomics Revealed Subtype-Specific Tumor Immune Microenvironments in Human Glioblastomas - Xiao, Yong; Wang, Zhen; Zhao, Mengjie; Deng, Yanxiang; Yang, Mingyu; Su, Graham; Yang, Kun; Qian, Chunfa; Hu, Xinhua; Liu, Yong; Geng, Liangyuan; Xiao, Yang; et al. (Frontiers in Immunology, 2022)
Human glioblastoma (GBM), the most aggressive brain tumor, comprises six major subtypes of malignant cells, giving rise to both inter-patient and intra-tumor heterogeneity. The interaction between different tumor subtypes and non-malignant cells to collectively shape a tumor microenvironment has not been systematically characterized. Herein we sampled the cellular milieu of surgically resected primary tumors from 7 GBM patients using single-cell transcriptome sequencing. A lineage relationship analysis revealed that a neural-progenitor-2-like (NPC2-like) state with high metabolic activity was associated with the tumor cells of origin. Mesenchymal-1-like (MES1-like) and mesenchymal-2-like (MES2-like) tumor cells correlated strongly with immune infiltration and chronic hypoxia niche responses. We identified four subsets of tumor-associated macrophages/microglia (TAMs), among which TAM1 co-opted both acute and chronic hypoxia response signatures, implicated in tumor angiogenesis, invasion, and poor prognosis. MES-like GBM cells expressed the highest number of M2-promoting ligands compared to other cellular states while all six states were associated with TAM M2-type polarization and immunosuppression via a set of 10 ligand-receptor signaling pathways. Our results provide new insights into the differential roles of GBM cell subtypes in the tumor-immune microenvironment that may be deployed for patient stratification and personalized treatment.